2019
DOI: 10.1038/s41598-019-40437-5
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of tumor shape, spiculatedness, correlates with tumor radiomic shape features

Abstract: Radiomics extracts high-throughput quantitative data from medical images to contribute to precision medicine. Radiomic shape features have been shown to correlate with patient outcomes. However, how radiomic shape features vary in function of tumor complexity and tumor volume, as well as with method used for meshing and voxel resampling, remains unknown. The aims of this study are to create tumor models with varying degrees of complexity, or spiculatedness, and evaluate their relationship with quantitatively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 33 publications
2
57
1
Order By: Relevance
“…In most cases, their objective is to differentiate between round, smooth, and regular lesions from spiculated, elongated, and irregular ones. Apart from volume, common shape features are compactness, elongation, rectangular fit, spherical disproportion, sphericity, surface area, and surface-to-volume ratio [24,28,29]. Clearly, shape features are more easily assessed at CT than PET due to the higher image resolution of the former.…”
Section: Shape Featuresmentioning
confidence: 99%
“…In most cases, their objective is to differentiate between round, smooth, and regular lesions from spiculated, elongated, and irregular ones. Apart from volume, common shape features are compactness, elongation, rectangular fit, spherical disproportion, sphericity, surface area, and surface-to-volume ratio [24,28,29]. Clearly, shape features are more easily assessed at CT than PET due to the higher image resolution of the former.…”
Section: Shape Featuresmentioning
confidence: 99%
“…22,[46][47][48][49] Identification of optimal classification methods and the best radiomic features for prognostic analyses in head and neck cancer patients may indeed broaden the scope of radiomics in precision oncology. [48][49][50][51][52] In this study we aim to investigate the potential value of radiomic features extracted from gross tumor volumes (GTVs) delineated on diagnostic CE-CT images of oropharyngeal cancer patients as potential biomarkers of HPV status.…”
Section: Introductionmentioning
confidence: 99%
“…However, some recent publications show that the volume could be an important predictor of treatment response . Similarly, recent studies to radiological features have reported that the shape of tumor, such as compactness, convexity, complexity, and nodularity, can be used as a prognostic factor for the treatment, but the researches on them are still lacking . Because there are limited published data examining tumor volume and shape, we have conducted a review of our institution's experiences analyzing patients who were initially treated with SRS alone.…”
Section: Introductionmentioning
confidence: 99%